Forensic nursing in the emergency department: the distance between nurses' performed role behaviors and their perception of behaviors' importance - Somayeh Zare Emami; Virginia A. Lynch; Marjan Banazadeh (BMC, 2024)
Abstract Background Emergency department nurses often deal with victims of violence and trauma. In the emergency department, the main focus is on saving lives and stabilizing patients' conditions. The next important task is to preserve any valuable evidence that could potentially help identify a crime. It is important to describe how nurses currently practice in the emergency department and perceive their role in caring for forensic patients. This study aimed to investigate the frequency of performance and perception of the importance of forensic nursing role behaviors among emergency department nurses as well as the correlation between mean scores of performance and perception. Methods This is a cross-sectional correlational descriptive study. This non-observational survey study used a questionnaire to investigate the frequency of performance and perception of the importance of forensic nursing role behaviors among 274 emergency department nurses. Results The total mean scores for frequency of performed behaviors and their perceived importance were 2.36±0.65 and 4.23±0.64 respectively. The overall mean scores of importance were significantly higher than frequency. There was a significant correlation between the frequency of performance and perception of the importance of twenty-eight items (twenty-four positive correlations and 4 negative correlations) (p<0.05). The frequency of performed behaviors positively correlated with participants' type of shift worked and their personal experiences of legal and judicial claims. The female gender of respondents positively correlated with behaviors' perceived importance. Conclusion The study revealed a significant discrepancy between the frequency of forensic nursing role behaviors performed and their perceived importance in the emergency department. This gap emphasizes the pressing requirement for forensic nursing subjects to be incorporated into graduate and undergraduate nursing curricula, as well as ongoing training programs and courses. It is crucial to establish and implement forensic nursing protocols for the care of trauma victims, and to foster collaboration between healthcare systems, law enforcement, and forensic investigators to streamline the process.